Dante, cinema, and television - Iannucci, Amilcare A. (Toronto Italian studies., 2004)
"Although Dante's influence in the literary sphere is well documented, little has been written on his role in the evolution of the visual media unique to our times, namely cinema and television. Dante, Cinema, and Television corrects this oversight." "The essays in this volume, written by scholars from a broad range of disciplines, examine the impact of the Divine Comedy on film and television, focusing on specific directors, writers, producers, and actors, from cinema's silent era to the present. The essays also consider individual productions and the different modes of appropriation used in cinema and television. Dante Cinema, and Television demonstrates the many ways, both subtle and bold, in which Dante's Divine Comedy has been given new life by cinema and television, and underscores Dante's vast legacy to modern culture."--Jacket.